Montelukast Use Decreases Cardiovascular Events in Asthmatics - Hoxha, Malvina; Tedesco, Calogero C.; Quaglin, Silvana; Malaj, Visar; Pustina, Linda; Capra, Valerie; Evans, Jilly F.; Sala, Angelo; Rovati, G. Enrico (Frontiers in Pharmacology, 2021)
Cysteinyl leukotrienes are proinflammatory mediators with a clinically established role in asthma and a human genetic and preclinical role in cardiovascular pathology. Given that cardiovascular disease has a critical inflammatory component, the aim of this work was to conduct an observational study to verify whether the use of a cysteinyl leukotriene antagonist, namely, montelukast, may protect asthmatic patients from a major cardiovascular event and, therefore, represent an innovative adjunct therapy to target an inflammatory component in cardiovascular disease. We performed an observational retrospective 3-year study on eight hundred adult asthmatic patients 18 years or older in Albania, equally distributed into two cohorts, exposed or nonexposed to montelukast usage, matched by age and gender according to information reported in the data collection. Patients with a previous history of myocardial infarction or ischemic stroke were excluded. In summary, 37 (4.6%) of the asthmatic patients, 32 nonexposed, and five exposed to montelukast suffered a major cardiovascular event during the 3-year observation period. All the cardiovascular events, in either group, occurred among patients with an increased cardiovascular risk. Our analyses demonstrate that, independent from gender, exposure to montelukast remained a significant protective factor for incident ischemic events (78% or 76% risk reduction depending on type of analysis). The event-free Kaplan–Meier survival curves confirmed the lower cardiovascular event incidence in patients exposed to montelukast. Our data suggest that there is a potential preventative role of montelukast for incident cardiac ischemic events in the older asthmatic population, indicating a comorbidity benefit of montelukast usage in asthmatics by targeting cysteinyl leukotriene-driven cardiac disease inflammation.